Effectiveness of prealbumin as an indicator of growth in neonates. Issue 42 (22nd October 2021) - Kim, Dong Hyun; Lee, Na Mi; Kim, Su Yeong; Yi, Dae Yong; Yun, Sin Weon; Chae, Soo Ahn; Lim, In Seok
Abstract : Abstract: We designed this study to assess the effectiveness of prealbumin as an indicator of growth as well as a nutritional marker in neonates. Between March 2017 and June 2019, we measured serum prealbumin concentrations of 80 neonates in neonatal intensive care unit at birth, postnatal day 14 and 28, and classified them into 3 groups (early preterm, late preterm, and term infants). And we examined correlation among prealbumin levels, nutritional intake, and anthropometric measurements (weight, length, and head circumference) in neonates. Prealbumin measured on the 14th postnatal day in early preterm infants showed significant correlations with the length, weight, and head circumference z-scores. Prealbumin levels increased with time in the late preterm and term groups. At birth, prealbumin levels were the lowest in late preterm babies, implying that they are nutritionally deficient and need nutritional support. At postnatal day 28, the prealbumin levels of many preterm infants did not reach those seen in term babies at birth, suggesting the presence of extrauterine growth restriction. Prealbumin can be considered as an indicator of sufficient growth in early preterm infants.